Implementation of Sea Highway Policy - Krisdiyanti, Faizah Fakriyah; Rianto, Budi; Lubis, Lunariana; Yuliansyah (Universitas Muhammadiyah Sidoarjo, 2023)
The concept of the sea toll program as the transportation of marine logistics with the aim of connecting major ports in the archipelago so that it is hoped that the existence of this sea toll will be able to connect ports to remote areas. This study examines the implementation of the policy of the Minister of Transportation of the Republic of Indonesia Number PM 23 of 2019 concerning Tariffs for Transporting Goods at Sea to Carry out Public Service Obligations carried out by the Tanjung Perak Main Port Authority. This study aims to describe and analyze the implementation of the sea toll policy at the Tanjung Perak Surabaya Main Port Authority Office along with the inhibiting and supporting factors. This research uses qualitative research methods with a case study approach with data collection techniques through interviews, observations, and documentation. This research uses qualitative research methods with a case study approach with data collection techniques through interviews, observations, and documentation. The results of the study using George Edward III's theory of public policy implementation show that the implementation of the Sea Toll Policy has been carried out well by the Tanjung Perak Surabaya Main Port Authority Office. The supporting factors are resources, bureaucratic structure and SOPs at the Tanjung Perak Main Port Authority Office which are already good to ensure the smooth operation of the sea toll, while the inhibiting factor is the imbalance of backloads on the sea toll route at the main port of Tanjung Perak, Surabaya.